Analysis of an Impulsive One-Predator and Two-Prey System with Stage-Structure and Generalized Functional Response - Xiangmin Ma; Yuanfu Shao; Zhen Wang; Xianjia Fang; Zhenguo Luo (Discrete Dynamics in Nature and Society)
An impulsive one-predator and two-prey system with stage-structure and generalized functional response is proposed and analyzed. By reasonable assumption and theoretical analysis, we obtain conditions for the existence and global attractivity of the predator-extinction periodic solution. Sufficient conditions for the permanence of this system are established via impulsive differential comparison theorem. Furthermore, abundant results of numerical simulations are given by choosing two different and concrete functional responses, which indicate that impulsive effects, stage-structure, and functional responses are vital to the dynamical properties of this system. Finally, the biological meanings of the main results and some control strategies are given.